Pigmented villonodular synovitis of the temporomandibular joint. evaluation of 12 patients from 2017 to 2023 - Vladimír, Machoň; Vasilis, Vlachopulos; Michal, Beňo; René, Foltán; Petr, Michl (Oral and maxillofacial surgery, 2025)
PURPOSE: The authors evaluated a cohort of 12 patients with histologically verified pigmented villonodular synovitis of the TMJ between 2018 and 2023. METHODS: The authors evaluated 12 patients (12 women). Only unilateral involvement was present in all patients. The mean age of the patients was 49.5 years. The authors focused on the evaluation of clinical symptoms, imaging findings, and arthroscopic findings. They also evaluated the effect of therapy, including the incidence of recurrence. The evaluation of therapy was performed at a minimum of 12 months after therapy and a maximum of 4.5 years after therapy. RESULTS: Pain was the predominant clinical symptom (12 patients, 100%). Therapy consisted of arthroscopy and open surgery. Radiographs were taken in all patients. In 5 patients (42%) the joint structures were without obvious pathological changes, in 7 patients (58%) there was a finding of irregularities on the joint head. Magnetic resonance imaging was performed in all patients, and in 10 cases (83%) there was a finding of joint space enlargement, effusion. Therapy consisted of TMJ arthroscopy with removal of pathological tissue. If the joint was completely filled with pathological tissue, after histological verification, open surgery with complete removal of joint structures and subsequent reconstruction of the TMJ was indicated. Recurrence of PVNS was not reported in the cohort. CONCLUSION: PVNS is an uncommon benign lesion affecting the TMJ. In the authors' study, pain was the predominant symptom and effusion was the predominant finding on magnetic resonance imaging. Long-term follow-up is appropriate in patients with proven PVNS. This is due to the risk of recurrence, which is also associated with the difficulty of complete repair of the lesion in the anatomically limited space of the TMJ. The authors recommend 1,3,6 months after surgery, and annually for the first 5 years after surgery. One, two, and five years after surgery, they recommend a follow-up MRI. The results of the study support the view that MRI should always be indicated in patients with pain of arthrogenic origin lasting more than 3 months, and if effusion is found, arthroscopy should always be the next step. This procedure will ensure early detection of PVNS.
Keywords: dospělí; Magnetic Resonance Imaging; Recurrence; Female; artroskopie; nemoci temporomandibulárního kloubu; Adult; ženské pohlaví; Pigmented villonodular synovitis; Synovitis, Pigmented Villonodular; lidé; magnetická rezonanční tomografie; recidiva; Temporomandibular Joint Disorders; TMJ; retrospektivní studie; Diffuse tenosynovial giant cell tumor; synovitida pigmentová vilonodulární; Male; lidé středního věku; Arthroscopy; mužské pohlaví; Retrospective Studies; Middle Aged; Humans